The effects of atorvastatin treatment on the mean platelet volume and red cell distribution width in patients with dyslipoproteinemia and comparison with plasma atherogenicity indicators--A pilot study - Kucera, Marek; Balaz, David; Kruzliak, Peter; Ciccocioppo, Rachele; Oravec, Stanislav; Rodrigo, Luis; Zulli, Anthony; Hirnerova, Eva; Sabaka, Peter; Komornikova, Andrea; Sabo, Jan; Slezak, Peter; et al. (Clinical biochemistry, 2015)
OBJECTIVES: The mean platelet volume (MPV) and red cell distribution width (RDW) have recently arisen interest because of their association with an increased cardiovascular risk. The aim of our study was, therefore, to determine whether an association exists between MPV, RDW and lipoprotein sub-fractions, and to show the impact of statin therapy on these new possible biomarkers of atherosclerotic risk. DESIGN AND METHODS: A cohort of 40 patients with hypercholesterolaemia (29 females, mean age 62.9±9 years), without previous hypolipidaemic treatment were enrolled. The patients were treated with atorvastatin 40 mg/day for 12 weeks. Total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density cholesterol (HDL-C), triglycerides (TG), LDL-C sub-fractions [large LDL-C 1-2 and small dense (sd)-LDL-C 3-7], apolipoproteins (apoA1, apoB), apoB/apoA1 ratio, atherogenic index of plasma (AIP), haematological parameters (including MPV, RDW) and safety parameters (renal, hepatic) were measured before and after 12 weeks of atorvastatin treatment. RESULTS: At baseline, a strong correlation between HDL-C, TG, sd-LDL-C, apoB, apoB/apoA1, and AIP with MPV (r=-0.55, p<0.001; r=0.57, p<0.001; r=0.73, p<0.001; r=0.41, p<0.05; r=0.52, p<0.001; r=0.61, p<0.001, respectively) and RDW (r=-0.49, p<0.001; r=0.62, p<0.001; r=0.67, p<0.001; r=0.41, p<0.05; r=0.43, p<0.05; r=0.65, p<0.001, respectively) was found. After 12 weeks of treatment with atorvastatin, MPV and RDW values underwent significant modification only in those patients displaying the strongest lipid-lowering effect. CONCLUSIONS: Values of MPV and RDW seem to reflect a pro-atherogenic lipoprotein profile mainly represented by the presence of sd-LDL-C.
Keywords: apolipoprotein B-100; střední objem trombocytu; apolipoprotein A-I; Erythrocyte Indices; Red cell distribution width; Dyslipidemias; Male; ateroskleróza; pilotní projekty; Mean platelet volume; Apolipoprotein B-100; Mean Platelet Volume; Aged; Small; mužské pohlaví; senioři; erytrocytární znaky; atorvastatin; lidé; dyslipidemie; ženské pohlaví; Atherosclerosis; Humans; anticholesteremika; Apolipoprotein A-I; Anticholesteremic Agents; Dense LDL; Atherogenic dyslipidaemia; Pilot Projects; Female; Atorvastatin; lidé středního věku; Middle Aged